Who killed the Red Baron [videorecording (DVD)] : a new look at who may have taken the Red Baron down - Nicholson, Peter (WGBH Educational Foundation, 2003)
An exciting new investigation of the Red Baron's death presents newly discovered documents that overturn the conventional theory of von Richthofen's demise. Featuring thrilling re-enactments of hair-raising duels between fragile fighters of World War I.